Generation Z’s Islamic Financial Planning: The Role of Islamic Financial Literacy and Parental Socialization - Hasanah, Nurul; Dede Abdul Fatah; Rizka Maulina Zulkarnain; Jiwa Ning Ayu Ramadhani; Putra Rizqi Dwi Saepullah (International Business Management - Universitas Ciputra, 2025)
The research is motivated by the phenomenon where Generation Z as generation that dominates Indonesian society does not have adequate financial planning. This is characterized by the Fear of Missing Out (FoMO) lifestyle which encourages Generation Z to spend money following existing trends and is not accompanied by good financial planning, many even involved online loans and bad credit. In Sharia Economic principles, it is important to avoid speculative behavior only driven by the desire to follow booming economic trends or opportunities. In line with the majority of people in Indonesia being Muslim, Generation Z must consider Sharia principles in carrying out financial planning to achieve sustainable financial stability. For this reason, the research aims to analyze the role of Islamic financial literacy and parental financial socialization toward Islamic financial planning among Generation Z. The method used is SEM-PLS. The research results show that Islamic financial literacy and parental financial socialization have a significant role for generation Z in carrying out financial planning based on a sharia perspective. The results of this research can be used as consideration for the policymakers, financial planners, and other related professionals in determining appropriate strategies and policies to encourage the realization of sustainable financial stability.